Majelis Tafsir Al-Qur'an (MTA) Religion Online for Ideological Da'wa Massification - Rina Sari Kusuma; Aprilia Dwi Isti Asmorowati (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2021)
Religious communities use the internet as a spiritual network to seek spiritual goals, and they interpret it through narratives shared through online spaces. This emphasizes the need for freedom and spiritual experiences so that they can share with others. So, people often associate their participation in online religion with a level of spirituality and confirmation of religious identity. Online religion seeks to adapt religion to form a network of spiritual interactions. This study discusses the use of the Internet by Majlis Tafsir Al-Qur'an (MTA) on the website www.mta.or.id in communicating ideology to the congregation. This research data collection uses the method of observation and documentation. The results of this study indicate that the use of digital technology by MTA is to promote ideology. MTA announces content regarding manhaj, terrorism, politics, the spirit of friendship / ukhuwah between members, and cooperation between scholars and the government.